THE EFFECT OF CORIANDER LEAVES EXTRACT ON THE DEGREE OF WISTAR RATS LIVER MICROSCOPIC DAMAGE WAS GIVEN MERCURIC CHLORIDE ORALLY - Ardiani, Zefania Regina; Sudaryanto, Sudaryanto; Istiadi, Hermawan; Hadi, Hadi (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background Mercury is a heavy metal that is widely used in various aspects of human life. However, mercury exposure can damage the liver. The high antioxidant found in coriander leaves is expected to be a solution to the problem in preventing liver damage due to mercury exposure. Aim Proving that administration of coriander leaf extract can reduce the degree of wistar rats liver microscopic damage due to mercury exposure. Methods Experimental study with post test only control group design for 14 days, used 24 male Wistar rats, divided randomly into 4 groups : C (-), C (+) (given mercury orally 10 mg / kgBW), X1 ( given mercury orally 10 mg / kgBW and coriander leaf extract 100 mg / kgBW) and X2 (given mercury orally 10 mg / kgBW and coriander leaf extract 200 mg / kgBW). On the 15th day, rats were terminated, the livers were harvested, microscopic preparations were made and stained with Hematoxylin-Eosin. Observed with a magnification of 400x in 5 different fields of view of each sample and were assessed using Manja Roenigk's score. Results Were obtained normal, mild damage, moderate damage, and severe damage respectively in the group: C (-): 80%, 20%, 0%, 0%; C (+): 0%, 3%, 67%, 30%; X1: 47%, 33%, 17%, 3%; X2: 77%, 23%, 0%, 0%. Spearman test found significant correlation (p = 0,000) with storng correlation ( r = 0.781) and the direction between the two variables is negative (-) . Kruskal Wallis test found significant differences (p = 0,000). Continued Mann Whitney test found significant differences between groups C (-) with C (+) (0,000), C (-) with X1 (0.004), C (+) with X1 (0,000), C (+) with X2 (0,000) ), and X1 with X2 (0.007) and the difference is not significant between C (-) and X2 (0.756). Conclusion Giving coriander leaves extract can reduce the degree of microscopic damage of Wistar rat liver due to mercury exposure.